Planejamento turístico - recreativo dos ambientes recifais das praias dos Seixas , Penha e Arraial (PB) - Melo, Rodrigo de Sousa (2006)
Reef environments attract yearly, a huge influx of tourists and recreationists who relentlessly pursue the leisure and knowledge of marine biodiversity, generating a significant profit for the economy of locales with peculiarities for tourism and recreation. However, the touristicrecreational activity at environmental reefs presents negative implications for local biodiversity if not associated to a planned process, mainly when not interrelated to social, economical, and biological dimensions throughout the planning. The reef environments at the beaches of Seixas, Penha, and Arraial (on southern littoral of João Pessoa, capital of Paraíba state, Northeast Brazil) have a lower touristic-recreational influx as compared to other reefs in the state of Paraíba. However, there is already a timid touristic promotion advertising the reefs of that part of southern littoral of Paraíba, mostly the ones at Penha beach. Therefore, it was aimed in the present dissertation to present a proposal concerning tourism planning and recreation on environmental reefs situated at the above-mentioned beaches, through zoning and evaluation of recreational carrying capacity. Firstly, it was performed a diagnosis of the areas by focusing socio-economic and biological aspects that generated important information for constructing the zoning proposal and estimating the recreational carrying capacity (Cifuentes, 1992). With respect to the biological aspects, it was performed an analysis of the distribution of the cnidofauna (with emphasis on scleractinian corals, zoanthidean, and calcareous hydroids) in areas with and without recreational use, through visual records carried out in October and November 2005. With respect to the socioeconomical aspects, the artisanal fishermen s way of life at the Penha beach was characterized, as well as their perceptions on several subjects, like the reef environments, conservation units, and excluded zones for fishing and tourism, by applying structured interviews as data collection technique which was carried out in June and July 2005. The following cnidarians species were identified: five scleractinians (Siderastrea stellata, Mussismilia harttii, Montastrea cavernosa, Agaricia agaricites and Porites astreoides; four zoanthideans (Palythoa caribaeroum, Protopalythoa variabilis, Zoanthus sociatus, and Zoanthus nymphaeus); and one calcareous hydroid (Millepora alcicornis). A greater biodiversity was observed in the area without recreational use. The fishermen at the Penha beach usually go to the reef areas for fishing and leisure, and they showed to be receptive to tourism and to the proposal for the establishment of a conservation unit in the area. Four zone types were defined for the zoning, with distinct uses and patterns, besides a buffer zone adjacent to the continent, since indirect impacts caused by local human actions may reduce the reefs health. The recreational carrying capacity was established from 26 visits per day or 4,680 per year carried out to the reefs of Seixas beach. It is proposed here a flexible and adjustable touristic-recreational planning for the study area, which might be partly modified throughout time, as new data on local biota, physicochemical parameters, and increase of touristic-recreational influx may come out